Current spring warming as a driver of selection on reproductive timing in a wild passerine. (12th February 2018) - Marrot, Pascal; Charmantier, Anne; Blondel, Jacques; Garant, Dany
Abstract: Evolutionary adaptation as a response to climate change is expected for fitness‐related traits affected by climate and exhibiting genetic variance. Although the relationship between warmer spring temperature and earlier timing of reproduction is well documented, quantifications and predictions of the impact of global warming on natural selection acting on phenology in wild populations remain rare. If global warming affects fitness in a similar way across individuals within a population, or if fitness consequences are independent of phenotypic variation in key‐adaptive traits, then no evolutionary response is expected for these traits. Here, we quantified the selection pressures acting on laying date during a 24‐year monitoring of blue tits in southern Mediterranean France, a hot spot of climate warming. We explored the temporal fluctuation in annual selection gradients and we determined its temperature‐related drivers. We first investigated the month‐specific warming since 1970 in our study site and tested its influence on selection pressures, using a model averaging approach. Then, we quantified the selection strength associated with temperature anomalies experienced by the blue tit population. We found that natural selection acting on laying date significantly fluctuated both in magnitude and in sign across years. After identifying a significant warming in spring and summer, we showed that warmer daily maximum temperatures in April were significantly associated with stronger selection pressures for reproductive timing. Our results indicated an increase in the strength of selection by 46% for every +1°C anomaly. Our results confirm the general assumption that recent climate change translates into strong selection favouring earlier breeders in passerine birds. Our findings also suggest that differences in fitness among individuals varying in their breeding phenology increase with climate warming. Such climate‐driven influence on the strength of directional selection acting on laying date could favour an adaptive response in this trait, since it is heritable. Abstract : This paper shows a strong spring warming (+2°C) in a wild Mediterranean passerine bird population. This warming strengthens the selection to breed earlier, which could favour an adaptive response in avian breeding phenology since laying date is a heritable trait.